Islamic spiritual leadership of kyai in fostering santris' entrepreneurial spirit and independence in boarding school - Abdul Karim; Oman Fathurohman; Sulaiman; Lina Marliani; Fakhri Fajrin Kurniawan; Firman Nugraha; Muaripin; Fitri Meliani; Mohammad Ridwan; Risbon Sianturi (Social Sciences and Humanities Open)
The spiritual leadership of kyai in Islamic boarding schools (IBS) plays a crucial role in shaping the character and independence of santri. This study focuses on understanding how the spiritual leadership of kyai at IBS of influences the development of entrepreneurial spirit and independence among santri, emphasizing the spiritual dimension within a managerial context. The objective of this research is to explore the role of kyai's Islamic spiritual leadership (ISL) in fostering the entrepreneurial spirit of santri and supporting their independence through an approach based on religious values in Al-Ishlah Bobos Cirebon, Indonesia. The data was examined via reduction, presentation, and conclusion-drawing using a qualitative approach with extensive interview data collection. Afterward, categorization and content analysis were carried out, and data was validated using source and time triangulation, transferability, and confirmability. The findings of the study indicate that kyai's ISL, grounded in religious values such as prayer (dua), role model (uswah hasanah), consultation (musyawarah), and muamalah based sharia, has a significant impact on fostering the entrepreneurial spirit and independence of santri. This research highlights that ISL not only nurtures the spiritual growth of santri but also boosts their entrepreneurial spirit and independence. The study provides valuable insights for developing leadership models in Islamic educational institutions by integrating spiritual values with entrepreneurial education for holistic student development.